STUDI KUANTITATIF TENTANG HUBUNGAN MINAT IBU HAMIL DALAM MENGKONSUMSI TABLET FE DENGAN KEJADIAN ANEMIA - Eka Deviany Widyawaty (Health Care Media, 2020)
Anemia is defined as a Hb level <11 g / dl in trimesters II and III. Based on WHO report (2013), MMR in the world is caused by preeclampsia 28%, bleeding 27%, eclampsia 14%, abortion 8%, infection 11%, delivery complication 9%, embolism 14%, anemia 51%. To determine the relationship of interest of pregnant women in consuming Ferrous Sulfat oral with anemia. Method: This study uses a quantitative approach with a cross-sectional study design, with analytic design. The subjects of TM II and III pregnant women were 36 people. The research instrument uses questionnaires and Health Card. The sampling technique uses total sampling technique. Statistical tests using Chi Square. The interest of pregnant women in consuming Fe tablets was 29 respondents with a high category (80.6%), respondents who were anemic 7 respondents (19.4%). Chi Square test analysis is known, r count = 5,063a. And ρ value = 0, 024 shows that r count of 5.063a> r table at df = 1 is 0.3291 then H0 is rejected so it can be concluded that the interest of pregnant women in consuming Fe tablets affects the incidence of anemia. Pregnant women who are obedient in consuming Fe tablets do not have anemia.